Perbandingan Pembelajaran Tatap Muka Dengan Electronic Learning (E-Learning) Terhadap Efektivitas Pembelajaran Percakapan Bahasa Mandarin Pada Mahasiswa Angkatan 2019 Di Universitas Widya Kartika - Ong Peter Leonardo; Sienny Kosasih (Universitas Widya Kartika, 2022)
One of the factors in determining the learning process can be said to be successful is in terms of the system used. This research is prepared to better understand the effects and influences of changes in the learning system that are currently occurring with the aim that in the future they can determine the system appropriately. In addition, the author also hopes to understand respondents to the system changes from the responses said. In this study, the author used a qualitative method with a sample of students of Widya Kartika University, Chinese Language Education Study Program class of 2019. In the results obtained, the author gives a percentage value so that the results can appear clearer. It can be said of the results of the study that face-to-face learning is more appropriate to be used in Chinese conversational learning compared to electronic learning.